The Aradidae (Insecta, Hemiptera, Heteroptera) of Argentina - Contreras, Eugenia Fernanda; Del Carmen Coscarón, María (Zootaxa, 2012)
In Argentina, 14 genera and 41 species are recorded, belonging to 5 subfamilies: Aneurinae, Aradinae, Calisiinae, Isodeminae and Mezirinae. Aneurosoma dissimile (Bergroth); Aneurus bosqui Kormilev; Aphleboderrhis comata Champion; Aphleboderrhis pilosa Stål; Aradus angustellus (Blanchard); Aradus brasiliensis Usinger; Aradus mexicanus Usinger; Aradus penningtoni Drake; Calisius confusus Kormilev; Dysodius lunatus (Fabricius); Iralunelus bergi (Kormilev); Iralunelus monrosi (Kormilev); Iralunelus subdipterus (Burmeister); Isodermus gayi (Spinola); Kormilevia dureti (Kormilev); Lobocara oblonga Bergroth; Mezira americana (Spinola); Mezira argentinensis (Kormilev); Mezira birabeni (Kormilev 1953); Mezira bonaerensis Kormilev; Mezira bruchi (Kormilev); Mezira formosa (Kormilev); Mezira granuliger (Stål); Mezira neonigripennis Kormilev; Mezira neonigripennis misionensis Kormilev; Mezira nigripennis Usinger; Mezira paragranuliger Kormilev; Mezira proseni Kormilev; Mezira regularis (Champion); Mezira reuteri (Bergroth); Mezira saltensis Kormilev; Mezira spissigrada Kormilev; Mezira tartagalensis Kormilev; Mezira vianai Kormilev; Neuroctenus centralis (Berg); Neuroctenus punctulatus (Burmeister); Neuroctenus subandinus Kormilev; Neuroctenus terginus (Stål); Notapictinus martinezi (Kormilev); Notapictinus sanmigueli (Kormilev); and Placogenys clarkei Kormilev.